The Wizard of Oz - Baum, L. Frank (Lyman Frank), 1856-1919. (New York : HarperFestival, 1999)
After being transported by a cyclone to the land of Oz, Dorothy and her dog are befriended by a scarecrow, a tin man, and a cowardly lion, who accompany her to the Emerald City to look for a wizard who can help Dorothy return home to Kansas.
6.8
3-6
3-6
1000
Keywords: Oz (Imaginary place) -- Juvenile fiction; Gale, Dorothy (Fictitious character) -- Juvenile fiction; Wizard of Oz (Fictitious character) -- Juvenile fiction; Oz (Imaginary place) -- Fiction; Gale, Dorothy (Fictitious character) -- Fiction; Wizard of Oz (Fictitious character) -- Fiction; Fantasy; Oz (Imaginary place) -- Fiction; Gale, Dorothy (Fictional character) -- Fiction; Wizard of Oz (Fictional character) -- Fiction; Fantasy fiction; Fantasy fiction